أثر إستخدام طريقة حل المشكلات في تدريس المسائل الرياضية اللفظية: دراسة تجريبية على تلاميذ الحلقة الثانية بمرحلة الأساس - محلية الخرطوم - سعد، أحلام حسب الرسول أحمد; حسن، الشفاء عبدالقادر; عبدالله، أحمد عبدالرحمن (جامعة السودان للعلوم والتكنولوجيا - عمادة البحث العلمى, 2015)
This study aimed at identifying the efficiency of Problem- solving approach using in teaching the verbally Math Problems/questions on the Pupils’ academic achievement of (2nd grade) at the primary education stage (Khartoum Locality). The researcher used the experimental approach, and population of this study comprised of the pupils of (5th class) at the primary education stage for academic year of 2014- 2015. The researcher intentionally selected a number of (40) pupils of the both gender, as a sample of this study, and being divided into two groups, one is experimental group with a number of (20) male pupils, and the other is (20) female pupils, who learned by the problem-solving approach, and the other learned by a traditional method. Then the researcher applied the test of cognitive achievement for the two mentioned groups in the end of academic term, in order to investigate into the efficiency of using problem-solving approach in teaching the verbally Math questions for pupils of (5th class) and their achievement in the Math subject. Based on the abovementioned, the researcher concluded some following results: The experimental female group, who learned by problem-solving approach outperformed the female group who learned by the traditional approach in their achievement findings, and the experimental male group, who leaned by the problem-solving approach also outperformed the male group, who learned by the traditional approach in their achievement findings. And showed an equal level for the achievement of female pupils, who learned by problem-solving approach, and the achievement level of male pupils who learned also by the same way.
هدفت هذه الدراسة للتعرف على أثر استخدام طريقة حل المشكلات في تدريس المسائل الرياضية اللفظية على التحصيل الدراسي لتلاميذ الحلقة الثانية بمرحلة التعليم الأساس (بمحلية الخرطوم). استخدم المنهج التجريبي، وتكون مجتمع الدراسة من تلاميذ وتلميذات الصف الخامس مرحلة الأساس للعام الدراسي 2014-2015. ولقد اختارت الباحثة عينة الدراسة قصدياً من(40) تلميذ و(40) تلميذة وقسمت إلى مجموعتين إحداهما تجريبية وقد بلغ عددها (20) تلميذ و(20) تلميذة درست بطريقة حل المشكلات والأخرى ضابطة وقد بلغ عددها (20) تلميذ و(20) تلميذة درست بالطريقة التقليدية. وقد قامت الباحثة بتطبيق الاختبار التحصيلي المعرفي إلى المجموعتين بعد انتهاء من فترة الدراسة. وذلك لمعرفة أثر استخدام طريقة حل المشكلات في تدريس المسائل الرياضية اللفظية في تحصيل تلاميذ الصف الخامس في مادة الرياضيات. وبناءً على ما تقدم توصلت الباحثة إلى النتائج التالية: تفوقت المجموعة التجريبية بنات والتي درست بطريقة حل المشكلات على المجموعة الضابطة بنات والتي درست بالطريقة التقليدية في نتائج التحصيل. وتفوقت المجموعة التجريبية بنين والتي درست بطريقة حل المشكلات على المجموعة الضابطة بنين والتي درست بالطريقة التقليدية في نتائج التحصيل. وتكافؤ مستوى تحصيل التلميذات اللائي درسن بطريقة حل المشكلات، ومستوى تحصيل التلاميذ الذين درسوا بذات الطريقة.
Keywords: التعليم الاساس -- الخرطوم (السودان) -- حل المشكلات -- الرياضيات اللفظية